Mekanisme Pasar dalam Perspektif Ekonomi Islam - Yenni Samri Juliati Nasution (Media Syari'ah, 2012)
The market is a natural mechanism for the exchange of goods and services. The market price is formed by a variety of factors which later formed the demand and supply of goods and services. Consumer demand is influenced by many factors, such as price, consumer income, tastes, expectations and level of mashlahah. Quote manufacturers also influenced by many factors, such as mashlahah, profits, and prices. Interaction of supply and demand will establish the balance point that can be changed from the demand side or the supply, either due to the deviation of structured or unstructured deviation. Perfectly competitive market can generate a fair price for the seller and the buyer. Therefore, if the market mechanism is interrupted, then the fair price will not be achieved. Islam puts the market at an important position in the economy, as well as concern about the concept of a fair price and perfect market mechanism.